Qalandar -name. Chapter 5. “The Praise of ‘Uthman, Commander of the Faithful” » - M.R. Ismagilova; D.A. Shagaviev (Золотоордынское обозрение)
The presented fragment is the next part of the translation of the medieval poetic text “Qalandar-name” of Abu Bakr Qalanadar Rumi, who was a Sufi scholar from the Crimea. This Chapter is devoted to praises to ‘Uthman Dhu-l-Nurayn (The Owner of Two Lights), the son-in-law of the Prophet Muhammad, the third of the four Righteous Caliphs (al-Khulafa al-Rashidun). Within the ten rows, the author mentions the virtues of ‘Uthman, making the main emphasis on piety and charity of this Prophet’s companion. The Persian text is translated by Milyausha Ismagilova, a postgraduate student. Translation’s edition and comments are supplied by Damir Shagaviyev, the Head of Department of History of Religions and Public Thought, Shihab al-Din al-Marjani’s Institute of History (Kazan). * Continuation. See the beginning in: Golden Horde Review, 2014, № 2(4), pp.243–252; № 3(5), pp.207–214; №4(6), pp.198–207; 2015. № 1, pp.171–177. Russian translation from Persian by a graduate student M.R. Ismagilova. Academic edition of the translation and comments by D.A. Shagaviev, Head of the Department of History of Religions and Social Thought at the Sh.Marjani Institute of History of AS RT (Kazan).